Tinjauan Penatalaksanaan Pemeriksaan Usg 2D Dengan Klinis Chronic Kidney Di Sease (CKD) Anemia Di Instalasi Radiologi Rumah Sakit Umum Dr. H. Abdul Moeloek Provinsi Lampung - Agata Rimba Angga Rita (Malahayati Nursing Journal, 2022)
ABSTRACT In the pre-survey result obtained from the entire radiological eximination in Ultrasound in April and June 2020 at the Radiology Installation at Abdul Moeloek Hospital, Lampung Province, where 352 patients had abdominal ultrasound examinations and 192 patients with Kidney Ultrasound Examination. Ultrasonography (ultrasound) is a diagnostic imaging (diagnostic imaging) to examine the organs where we can study the shape, anatomical size, movement, and the relationship with the surrounding tissue. CKD Kidney disease that has lasted a long time, causing kidney failure. The kidneys filter waste and excess fluid from the blood. If the kidneys do not function, waste accumulates, anemia is the most common complication in chronic kidney disease (CKD). To find out the management procedure of 2D ultrasound examination with clinical ckd anemia, To find out the management technique of 2D ultrasound examination with clinical CKD anemia, To find out the results of the picture after the 2D ultrasound examination was carried out with clinical CKD anemia. This study uses descriptive qualitative method. A sample of 1 patient was a patient who underwent procedure of 2D ultrasound examination with clinical ckd anemia the radiology Installation of Hospital Dr. H. Abdul Moeloek Province of lampung. Data is obtained from literature studies, observations, and interviews. During the kidney ultrasound examination with clinical CKD anemia at the Radiology Installation of Abdul Moeloek Hospital, Lampung Province, the equipment used for this examination consisted of a 7.5 MHz linear transducer, preparations for only preparing special jelly and ultrasound tissue, and special preparations, namely the abdomen on fasting 8 hours before examination. Management of renal ultrasound with clinical anemia CKD at the Radiology Installation of RSUD Dr. Hi. Abdul Moeloek Lampung Province is quite effective, namely to show abnormalities in the organ to be examined and the surrounding tissue. Keywords: 2D ultrasound, CKD, Anemia Clinical  ABSTRAK Pada hasil pre-survey, didapatkan dari keseluruhan pemeriksaan radiologi menggunakan USG 2D pada bulan April, dan juni 2020 di Instalasi Radiologi RSUD Abdul Moeloek Provinsi Lampung, terdapat pemeriksaan USG Abdomen sebanyak 352 pasien dan 192 pasien Pemeriksaan USG Ginjal. Ultrasonografi (usg) merupakan salah satu imaging diagnotic (pencitraan diagnostik) untuk memeriksa alat alat tubuh dimana kita dapat mempelajari bentuk, ukuran anatomi,gerakan,serta hubungan dengan jaringan sekitarnya. Untuk mengetahui bagaimana persiapan pasien dalam penatalaksanaan pemeriksaan USG 2D dengan  klinis CKD anemia, Untuk mengetahui teknik penatalaksanaan pemeriksaan USG 2d dengan klinis CKD anemia, Untuk mengetahui hasil gambaran setelah di lakukan penatalaksanaan pemeriksaan USG 2D dengan klinis CKD anemia. Penelitian ini menggunakan metode Deskriptif Kualitatif. Sampel sebanyak 1 orang pasien yaitu pasien yang melakukan pemeriksaan  USG 2D dengan  klinis CKD anemia di Instalasi Radiologi RSUD Dr.H. Abdul Moeloek provinsi Lampung. Data diperoleh dari studi pustaka, observasi dan wawancara. Pada pemeriksaan USG Ginjal dengan klinis CKD Anemia di Instalasi Radiologi RSUD Abdul Moeloek Provinsi Lampung, persiapan alat yang digunakan pada pemeriksaan ini terdiri dari transduser linier 7,5 MHz, persiapan bahan hanya menyiapkan jelly khusus dan tissue USG, dan persipan khusus yaitu Abdomen atas puasa 8 jam sebelum pemeriksaan. Penatalaksanaan USG Ginjal dengan klinis CKD Anemia di Instalasi Radiologi RSUD Dr. Hi. Abdul Moeloek Provinsi Lampung cukup efektif yaitu untuk memperlihatkan kelainan- kelainan pada organ yang akan di periksa serta jaringan di sekitarnya. Kata Kunci: USG 2D, Ginjal, Anemia Klinis